Comparison of Whole Eye versus First-Surface Astigmatism in Down Syndrome. Issue 7 (July 2015) - Knowlton, Rachel; Marsack, Jason D.; Leach, Norman E.; Herring, Ralph J.; Anderson, Heather A.
ABSTRACT Purpose Subjects with Down syndrome have structural differences in the cornea and lens, as compared with the general population. This study investigates objectively measured refractive and corneal astigmatism, as well as calculated internal astigmatism in subjects with and without Down syndrome. Methods Refractive (Grand Seiko autorefraction) and anterior corneal astigmatism (difference between steep and flat keratometry obtained with Zeiss Atlas corneal topography) were measured in 128 subjects with Down syndrome (mean [±SD] age, 24.8 [±8.7] years) and 137 control subjects without Down syndrome (mean [±SD] age, 24.9 [±9.9] years), with one eye randomly selected for analysis per subject. Refractive astigmatism and corneal astigmatism were converted to vector notation (J0, J45) to calculate internal astigmatism (Refractive − Corneal) and then converted back to minus cylinder form. Results Mean [±SD] refractive astigmatism was significantly greater in subjects with Down syndrome than in control subjects (−1.94 [±1.30] DC vs. −0.66 [±0.60] DC, t = −10.16, p < 0.001), as were mean corneal astigmatism (1.70 [±1.04] DC vs. 1.02 [±0.63] DC, t = 6.38, p < 0.001) and mean internal astigmatism (−1.07 [±0.68] DC vs. −0.77 [±0.41] DC, t = −4.21, p < 0.001). A positive linear correlation between corneal and refractive astigmatism was observed for both study populations for both the J0 and J45 vectors (p < 0.001 for all comparisons; R2 range, 0.31 to 0.74). The distributions of astigmatism orientation differed significantly between the two study populations for comparisons of corneal and calculated internal astigmatism (χ2, p < 0.007), but not refractive astigmatism (p = 0.46). Conclusions This study demonstrates that corneal astigmatism is predictive of overall refractive astigmatism in subjects with Down syndrome, as it is in the general population. The greater magnitudes of astigmatism and wider variation of astigmatism orientation in subjects with Down syndrome for refractive, corneal, and calculated internal astigmatism are likely attributable to previously reported differences in the structure of the cornea and internal optical components of the eye from that of the general population.